Medication Adherence to Oral Hypoglycemic Agents Among Type II Diabetic Patients and Their Clinical Outcomes with Special Reference to Fasting Blood Glucose and Glycosylated Hemoglobin Levels - Shrestha, SS; Shakya, R; Karmacharya, BM; Thapa, P (Kathmandu University Medical Journal, 2015)
Background Oral hypoglycemic agents (OHAs) are the major treatment for people with type 2 diabetes mellitus (DM2). However, non-adherence to OHAs remains as one of the main reasons for poor glycemic control. Objectives To assess the adherence pattern to OHAs and clinical outcomes with special reference to fasting blood glucose (FBG) level and glycosylated hemoglobin (HbA1c) levels. Methods Informed consent was obtained from patients fulfilling the criteria and from the patient party in case of incapacitated patients. Information was obtained by interviewing them and filled in the appropriate questionnaire. All the medical information of the patients was obtained from the medical case records and laboratory reports. Results OHAs had been discontinued by 25% of patients. Overall 38% had ever discontinued and/ or often missed OHAs. Intentional discontinuation of OHAs attributed for 72% of the patients, followed by forgetfulness (42.9%), carelessness (30.6%), and hypoglycemia, (24%). There were 50.50% patients who had uncontrolled FBG (>130 mg/dl) level and 39% had uncontrolled HbA1c (≥ 7%) level. Taking reference age group 51-60 years, control of FBG level was found to be statistically associated with the decreasing age group (p = 0.006, OR = 4.8) as well as increasing age group (p = 0.008, OR = 4.034). There was significant association between controlled HbA1c level and patients’ knowledge about the precautions to be taken while using OHAs (p = 0.044, OR = 4). However, there was no significant association between glycemic control and OHAs adherence. Conclusion Majority of the patients who had missed OHAs attributed it to forgetfulness. Hypoglycemia may also be one of the contributing factors for poor adherence to OHAs. However no association was found between adherence and various other factors like age groups, treatment complexity, health literacy and social or family support. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12508 Kathmandu Univ Med J 2013; 43(3):226-232